Avaliação da detecção de casos de tuberculose no contexto da atenção primária à saúde - Härter, Jenifer (2013)
Brazil displays a reduction in epidemiological markers related to tuberculosis (TB) over the last ten years. While the level of attention of the health system, the primary health care serves as the gateway to health care, coordinating and directing health care, recommended as crucial space for intervention in disease control. The detection of TB cases is the main strategy aimed at controlling the disease nationwide, it involves the identification of respiratory symptoms (RS); the diagnosis of TB; conduct adopted with the individual and confirmation of the diagnosis. The objective was to evaluate the detection of TB cases in the Family Health Units and Traditional Basic Health Units in the perspective of health professionals in Pelotas /RS. We used the elements of the process (problem recognition, individual and collective handling) and structure (personnel, facilities / equipment and organization) to evaluate the performance of the services, understanding it as the implementation of actions to detect cases, considering the presence of the necessary structure for the development of actions. The study is a cross-sectional quantitative one, conducted with 276 health professionals from 51 units of Pelotas / RS in the period April to August 2012. The variables of interest comprise a pre-tested adaptation of the questionnaire to evaluate performance of primary care services in TB control. For analysis, the data were Stratified by type of health primary care service. Multiple Correspondence and absolute frequency analysis were performed. The family health unit was associated with: identification of professionals prepared to RS; presence of sputum spot and smear request forms; conducting clinical evaluation and smear request; realization of collective action in the community. It was observed that the health unit family sometimes performed RS search within unity and community; almost never performed health education on TB in the community. The traditional basic health unit was associated with: professional and clinical update without testing and without security to identify the RS ; lack of sputum pot and smear request form; professionals who didn t perform clinical evaluation, didn t requested smear, and didn t perform collective actions in the community. Therefore, detection of TB cases in primary health care, particularly at the BHU, showed weaknesses in the structure and development of actions to detect cases of the disease in the city.